2021
DOI: 10.3390/plants10010140
|View full text |Cite
|
Sign up to set email alerts
|

Gentiana asclepiadea L. from Two High Mountainous Habitats: Inter- and Intrapopulation Variability Based on Species’ Phytochemistry

Abstract: Natural populations of Gentiana asclepiadea L., located at two mountainous sites, were HPLC-analyzed regarding the contents of six representative secondary metabolites. The contents of swertiamarin (SWM), gentiopicrin (GP), sweroside (SWZ), mangiferin (MGF), isoorientin (ISOOR), and isovitexin (ISOV) were determined in six populations (three per study site), and separately for aboveground and belowground plant parts. PCA showed a clear separation of four groups according to the contents of the analyzed seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The structures were identified as depressine (1) [27], gentiopicroside (2) [28], loganic acid (3) [29], isoorientin (4) [30], isovitexin (5) [31], mangiferin (6) [32] and adenosine (7) [33] by comparison of their spectroscopic data with those reported in the literature. In previous studies, compounds 2-6 were detected in G. asclepiadea extracts by HPLC analysis, while the presence of 1 was tentatively identified [34][35][36]. In our very recent study, compounds 2-6 were also reported from another Gentiana species, G. cruciata [25].…”
Section: Structure Elucidation Of the Isolatesmentioning
confidence: 69%
“…The structures were identified as depressine (1) [27], gentiopicroside (2) [28], loganic acid (3) [29], isoorientin (4) [30], isovitexin (5) [31], mangiferin (6) [32] and adenosine (7) [33] by comparison of their spectroscopic data with those reported in the literature. In previous studies, compounds 2-6 were detected in G. asclepiadea extracts by HPLC analysis, while the presence of 1 was tentatively identified [34][35][36]. In our very recent study, compounds 2-6 were also reported from another Gentiana species, G. cruciata [25].…”
Section: Structure Elucidation Of the Isolatesmentioning
confidence: 69%
“…This finding was in agreement with the results of Mihailović et al (2013) [ 3 ], who detected mangiferin only in the aboveground parts of willow gentian, while it was absent in the underground parts. Popović et al (2021) also reported the organ-specific distribution of secondary metabolites of willow gentian and that mangiferin is dominantly accumulated in the aboveground plant parts [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Serbian common names, “grass of stomach” and “grass of jaundice”, indicate the great confidence of the local population in the medicinal properties of willow gentian [ 5 ]. Furthermore, Gentiana species attract attention since they inhabit high mountainous regions where the local population has limited access to official healthcare and, therefore, they are forced to rely on their own experiences in self-medication [ 7 ]. This is consistent with the report by Olennikov et al (2015) [ 8 ] that nomadic people of Siberia use some Gentian species as bitter teas for the treatment of digestive disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their production depends on the physical and chemical properties of the ecosystem, like precipitation, temperature, and edaphic conditions, but also elevation [ [1] , [2] , [3] , [4] , 8 , 9 ]. Therefore, wild aromatic plants present high chemical polymorphisms in response to the contrasted environmental conditions and geographical distances of their different populations, leading to an important intra- and inter-population chemical variability [ [8] , [9] , [10] , [11] , [12] , [13] ]. In the same way, the variability of the essential oil (EO) composition of the natural populations is related also to various environmental, geographical, and genetic factors, which influence, in combination or independently, the essential oils (EOs) quantitative and qualitative composition and properties [ [1] , [2] , [3] , 9 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 99%